Climate change adaptation for hydrology and water resources. FINADAPT Working Paper 6 - Silander, Jari; Vehviläinen, Bertel; Niemi, Jorma; Arosilta, Anna; Dubrovin, Tanja; Jormola, Jukka; Keskisarja, Ville; Keto, Antton; Lepistö, Ahti; Ollila, Markku; Pajula, Heikki; Pitkänen, Heikki; et al. (Finnish Environment Institute, 2013)
The most important effect of climate change on hydrological regimes in Finland is the change in seasonal distribution of runoff. Winter runoff is expected to increase considerably due to an increase in snowmelt and rainfall, while spring floods are estimated to decrease in southern Finland. In northern Finland spring floods are expected to increase during the next few decades due to increased snowfall, but then to decline over the longer term with continuous warming. Yearly runoff is estimated to change from -5 % to 10 %. Decreases are predicted for catchments with a large lake surface which enhance lake evaporation; increases are through winter runoff. In winter excess water from snowmelt and rainfall can cause winter floods, especially large central lakes Saimaa, Päijänne and Näsijärvi will be more frequently flooded. Extreme runoff events are projected to be more frequent due to increased maximum precipitation. Impacts and adaptation to these effects in hydrological cycle are described in this publication.